PERILAKU SARAPAN PAGI DAN KAITANNYA DENGAN PRESTASI BELAJAR SISWI SEKOLAH MENENGAH PERTAMA DI SMPN 2 DEPOK - Ari Nofitasari; Rina A Anggorodi; Triyanti Triyanti (Jurnal Kesehatan Masyarakat Andalas, 2009)
For students, breakfast is very important to improve their concentration to study and enable them to absorb materialsdelivered in schools easier thereby their qualityof study achievement improve. Hunger because of not havingbreakfast beforegoing to school will impact on students 'consentration to study, decrease their ability to solve problems and often lead to difficulties on answer mathematic quiz. This study is aimed to understand breakfast behavior and important factors determining the qualityof study achievement of students in SMPN 2 Depok. The methodemployed in this studv is cross Sectional Design. Sample for the study covering 217 female students. Data was analyzed using logistical regression test. The finding of this research shows the proportion offemale students who have breakfast is 58,5 %. The result of statistical tests shows that there is a colored correlation between nutritional knowledge, breakfast availability, level of mothers' education and the quality of study achievement with female students' breakfast behavior (P 0,05). Factors determining breakfast behavior is nutritional knowledge of female students, availability of breakfastand mothers 'level of education. Factors determining breakfast behavior is nutritionalknowledgeoffemale students, availabilityof breakfast and mothers level of education. The dominant factor that correlates to breakfast behavior is mother’s level of education.